Exploring the differences between an Omani traditional and renaissance jewelry from the perspective of an old generation of Omani women (Al-Academy, 2024)
This paper will attempt to explore the history of women jewelry in Oman and to know the differences between traditional and contemporary jewelry from old generation women. The paper discovers the hidden stories of old jewelry piece that owned by Omani women. Although jewelry has moving into trends and fashion styles throughout the centuries, women keep their old jewelries because of its uniqueness. By using methodology of semi-structures interviews, it classifies them under four main categories which are jewelry maker, weight versus cost, places to wear and traditional designs and inspirations. Understanding the historical context and provenance of a jewelry piece in a particular era can provide valuable context for Omani cultural and traditions. Moreover, gathering information about the previous owners of antique jewelry can offer valuable clues about the jewelry's age and reflect so much more to us than just being ornamental items.